Determining next best view based on occlusion information in a single depth image of visual object. (29th December 2016) - Zhang, Shihui; Miao, Yuxia; Li, Xin; He, Huan; Sang, Yu; Du, Xuezhe
How to determine the camera's next best view is a challenging problem in vision field. A next best view approach is proposed based on occlusion information in a single depth image. First, the occlusion detection is accomplished for the depth image of visual object in current view to obtain the occlusion boundary and the nether adjacent boundary. Second, the external surface of occluded region is constructed and modeled according to the occlusion boundary and the nether adjacent boundary. Third, the observation direction, observation center point, and area information of external surface of occluded region are solved. And then, the set of candidate observation directions and the visual space of each candidate direction are determined. Finally, the next best view is achieved by solving the next best observation direction and camera's observation position. The proposed approach does not need the prior knowledge of visual object or limit the camera position on a specially appointed surface. Experimental results demonstrate that the approach is feasible and effective.